Technoeconomic analysis for biofuels and bioproducts. (February 2021) - Scown, Corinne D; Baral, Nawa Raj; Yang, Minliang; Vora, Nemi; Huntington, Tyler
Graphical abstract: Highlights: Technoeconomic analysis involves process design and simulation. New studies have expanded to incorporate market size, policy incentives, and use. There is a trend toward lightweight open-source TEA tools. Inclusion both fuels and co-products complicates methods and performance metrics. Integration of TEA with high-throughput experimental pipelines is promising. Abstract : Technoeconomic analysis (TEA) is an approach for conducting process design and simulation, informed by empirical data, to estimate capital costs, operating costs, mass balances, and energy balances for a commercial scale biorefinery. TEA serves as a useful method to screen potential research priorities, identify cost bottlenecks at the earliest stages of research, and provide the mass and energy data needed to conduct life-cycle environmental assessments. Recent studies have produced new tools and methods to enable faster iteration on potential designs, more robust uncertainty analysis, and greater accessibility through the use of open-source platforms. There is also a trend toward more expansive system boundaries to incorporate the impact of policy incentives, use-phase performance differences, and potential impacts on global market supply.